(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2013)
In this paper I want to claim that “politicization of values” will lead to individualization in society, in the long run, and further that this process will amount to a more personal form of legislation. Looking at the example of Turkey, I will employ Habermas’ theories of “communicative action” and “discursive law”, in order to explain how this process is taking place. My main claim is that the theory of communicative action explains how allowing values to be manifested in the public sphere leads to the rationalization of those values, and subsequently to individualization within the society.